Campylobacter fetus impairs barrier function in HT‐29/B6 cells through focal tight junction alterations and leaks. Issue 1 (29th June 2017) - Bücker, Roland; Krug, Susanne M.; Fromm, Anja; Nielsen, Hans Linde; Fromm, Michael; Nielsen, Henrik; Schulzke, Jörg‐Dieter
Abstract: Infections by Campylobacter species are the most common foodborne zoonotic disease worldwide. Campylobacter jejuni and C. coli are isolated most frequently from human stool samples, but severe infections by C. fetus (Cf), which can cause gastroenteritis, septicemia, and abortion, are also found. This study aims at the characterization of pathological changes in Cf infection using an intestinal epithelial cell model. The Cf‐induced epithelial barrier defects appeared earlier than those of avian Campylobacter species like C. jejuni/C. coli . Two‐path impedance spectroscopy (2PI) distinguished transcellular and paracellular resistance contributions to the overall epithelial barrier impairment. Both transcellular and paracellular resistance of Cf‐infected HT‐29/B6 monolayers were reduced. The latter was attributed to activation of active anion secretion. Western blot analysis showed no decrease in tight junction (TJ) protein expression (claudin‐1, ‐2, ‐3, and ‐4) but showed redistribution of claudin‐1 off the TJ domain. In addition, Cf induced epithelial cell death, cell detachment, and lesions (focal leaks), as the result of which macromolecule flux (10‐kDa dextran) was increased in Cf‐invaded cell monolayers. In conclusion, barrier dysfunction from Cf infection was due to TJ protein redistribution, cell death induction, and leak formation, resulting in bacterial translocation, ion leak flux, and antigen uptake (leaky gut).